Sound Governance Pada Aplikasi E-Samsat Provinsi Riau - Nurul Huda; Geovani Meiwanda (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
Motor vehicle tax is one of Riau's Regional Original Income (PAD), and in the process of implementing the government's motor vehicle tax collection has improved its governance system which refers to Sound Governance. Payment of motor vehicle taxes that were previously manual but have now switched to electronics where this system has been done since 2018. In its implementation there is an increase in users but sometimes the decline still occurs. The research could eventually find several things related to the change in motor vehicle tax payments from manual to digital in the perspective of Sound Governance by Tjahjanulin Domai. In this case the researcher uses qualitative research methods with a descriptive approach. The results of this study from Sound Governance showed that the implementation of digital-based motor vehicle tax payments has not run optimally because the application of Sound Governance dimensions in the implementation of E-Samsat application of Riau Province has not worked effectively and efficiently and there are still obstacles to the implementation of socialization strategies and infrastructure facilities.